EFFICIENCY OF INNOVATIVE BUSINESS MANAGEMENT BASED ON BIG DATA: CHANGING THE ROLE OF MANAGERS - GANUSHCHAK-YEFIMENKO, Lyudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The presented work emphasizes that in the modern world, technologies are rapidly developing, globalization and digitalization are becoming the key to effective management of innovative business and an integral part of the successful activities of companies. Innovations are the main engine of economic growth and competitiveness, and the ability to quickly adapt to market changes is becoming a key factor in achieving leadership positions. One of the important aspects that determine the success of innovative business models is the use of big data, which allows you to make more informed decisions, increase the efficiency of management processes and optimize resource costs. That is why the purpose of the presented work is to determine the main components of effective management of innovative business based on big data and how this process can affect the personnel component and managers as a whole. To achieve the objectives of the study, both qualitative and quantitative analysis methods are used, aimed at studying the impact of data analytics on the effectiveness of business management. The research methods include collecting data from surveys, case studies and analyzing examples of corporate practice, which allows you to get a comprehensive picture of this phenomenon. Qualitative analysis includes case studies of companies that actively use data analytics to improve management efficiency. Quantitative analysis is based on the collection and processing of statistical data, such as productivity growth, cost reduction, and revenue growth through the use of data analytics. Surveys of executives of large companies are also an important research tool. Thus, the combination of qualitative analysis through case studies and quantitative analysis through statistical data, as well as the use of surveys of corporate leaders, create the basis for a comprehensive understanding of the impact of analytics on business management. These methods allow not only to assess current results, but also to offer specific solutions to overcome the problems associated with the implementation of analytical approaches in corporate management. Thus, big data provides companies with the opportunity to obtain valuable information from various sources, analyze trends, and model future development scenarios. This allows not only to respond quickly to changes in the environment, but also to proactively form strategies to support innovative potential. This paper examines the aspects of the effectiveness of innovative business management based on big data, identifies the advantages, challenges and prospects of using this approach to achieve competitive advantages and business sustainability in conditions of uncertainty.
Keywords: innovatively active enterprises; innovative business models; big data; digital transformations; innovative enterprises; digital technologies; management; personnel management; analytics system; analytics; manager; personnel; business models; business model transformation; innovative activity; innovative policy